Pengaruh Kompetensi Sumber Daya Manusia Dan Peran Audit Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Sawahlunto) - Lola Septiana; Efrizal Syofyan; Henri Agustin (Wahana Riset Akuntansi, 2017)
This research aims to determine: (1) the effect of the the Human Resources competencies toward the Local Government Finance Report quality, (2) the effect of the role of internal audits toward the Local Government Finance Report. Type of this research is causative. The population of the reseach were 27 units of Satuan Kerja Perangkat Daerah (SKPD) in Sawahlunto. The technique of sample collection is total sampling method. The sources of the data of this research is the primary data. The technique of the the data collection is questionnaires. The data were analyzed using multiple regression analysis using SPSS version 20. The results of the reseach showed that: (1) Human resources competencies positively and significantly effect on the quality of LKPD, (2) the role of internal audit is does not a positively and significantly effect on the quality of LKPD. Suggestions of this are: to the next researchers should be able to use the model of other researches, such as, using an intervening variable, moderating variables, or control variables and replace other independent variables which may be affect the quality of financial statements and are expected to expand the area of researches.Keywords: local government financial statements, human resources, internal audit.